(untitled) (Research, Society and Development, 2021)
Introduction: urban mobility is understood as the daily ability to move people and goods in the urban space safely and in a time considered appropriate. Recently, the pandemic situation was gradually eased and the economic and social recovery plan was put on the agenda by the government during the post-epidemic period. In these circumstances, the urban transport system plays a crucial role in the process of social and economic recovery as a basic guarantee of the city. Therefore, greater attention must be paid to the impacts of the COVID-19 pandemic on the urban transport system, as well as on travel behavior. Objective: to highlight the impacts caused by the COVID-19 pandemic on urban mobility. Methodology: this is a narrative review of the literature, with studies linked to the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Library Health Virtual (BVS) and EBSCO Information Services. Results: some impacts on urban mobility could be observed due to the high degree of contagion of the new coronavirus and, therefore, the need to stay at home and keep a minimum distance. These are initially social, economic or environmental impacts, but they have a strong relationship with urban mobility. In general, there has been a drastic decrease in locomotion in cities, which have found themselves empty, and there is fear of returning to normal activities as isolation is eased. Final considerations: the COVID-19 pandemic caused countless changes in the lives of the world population. In urban mobility it was no different. With the closing of businesses considered non-essential, the suspension of classes and the installation of teleworking systems, a large part of daily commuting was interrupted and/or modified. Measures such as the installation of public transport subsidy policies, the expansion of bicycle lanes, the application of actions to discourage the use of individual motorized transport, improvement in public safety and the circulation of pedestrians and cyclists, etc., proved to be urgent during the quarantine, not only to create minimal conditions for active mobility, but also to improve the quality of life of the population as a whole.